PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PENGGUNA APLIKASI JAMRIDE DI PENAJAM PASER UTARA - Ayu Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the simultaneous and partial influence of brand image variables and service quality on consumer satisfaction of users of the Jamride application in North Penajam Paser. The brand image (Xı) and service quality (X2) variables are independent or independent variables in this research and the consumer satisfaction variable (Y) is the dependent or bound variable in this research. The type of research used in this research is quantitative research. The technique used was Non Probability Sampling using the Purposive Sampling method with a sample size of 100 respondents. The data analysis technique used is multiple linear regression analysis. The conclusion of this research is that the brand image and service quality variables simultaneously have a positive and significant effect on consumer satisfaction using the Jamride application in North Penajam Paser, the brand image and service quality variables partially have a positive and significant effect on consumer satisfaction using the Jamride application in North Penajam Paser .